Acupuncture therapies for cancer-related fatigue: A Bayesian network meta-analysis and systematic review - Tian, Hao; Chen, Yunhui; Sun, Mingsheng; Huang, Liuyang; Xu, Guixing; Yang, Chunyang; Luo, Qin; Zhao, Ling; Wei, Zheng; Liang, Fanrong (Frontiers in Oncology, 2023)
Background Cancer-related fatigue (CRF) is one of the most commonly reported symptoms impacting cancer survivors. This study evaluated and compared the effectiveness and safety of acupuncture treatments for CRF. Methods We searched PubMed, Embase, Web of Science, Cochrane Library, China Biology Medicine China National Knowledge Infrastructure, China Science and Technology Journal Database, and WanFang Database from inception to November 2022 to identify eligible randomized controlled trials (RCTs) comparing acupuncture treatments with sham interventions, waitlist (WL), or usual care (UC) for CRF treatment. The outcomes included the Cancer Fatigue Scale (CFS) and Pittsburgh Sleep Quality Index (PSQI), and pair-wise and Bayesian network meta-analyses were performed using STATA v17.0. Results In total, 34 randomized controlled trials featuring 2632 participants were included. In the network meta-analysis, the primary analysis using CFS illustrated that point application (PA) + UC (standardized mean difference [SMD] = −1.33, 95% CI = −2.02, −0.63) had the highest probability of improving CFS, followed by manual acupuncture (MA) + PA (SMD = −1.21, 95% CI = −2.05, −0.38) and MA + UC (SMD = −0.80, 95% CI = −1.50, −0.09). Moreover, the adverse events of these interventions were acceptable. Conclusion This study demonstrated that acupuncture was effective and safe on CRF treatment. However, further studies are still warranted by incorporating more large-scale and high-quality RCTs. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42022339769.